Epigenetic control of mesenchymal stem cells orchestrates bone regeneration - Wang, Xiaofeng; Yu, Fanyuan; Ye, Ling (Frontiers in Endocrinology, 2023)
In recent studies, the vital role of mesenchymal stem cells (MSCs) in bone regeneration has been revealed. Both in self-healing bone regeneration processes and biomaterial-induced healing of bone defects beyond the critical size, MSCs show multiple functions, including osteogenic differentiation and thus providing seed cells. However, MSCs’ important function in bone regeneration can be significantly affected by adverse factors such as drug intake and body senescence. Currently, several modalities have been developed to regulate the phenotype of MSCs to promote the bone regeneration process. Epigenetic regulation has received much attention because of its heritable nature. Indeed, epigenetic regulation of MSCs has been shown to be involved in the pathogenesis of a variety of disorders of bone metabolism, and studies using epigenetic regulation to treat disease are also being reported. However, the impact of epigenetic regulation on MSCs has yet to be fully understood. This review focus on recent advances in the effects of epigenetic regulation on osteogenic differentiation, proliferation, and cellular senescence in MSCs. We intend to illustrate how epigenetic regulation of MSC orchestrates the process of bone regeneration.